The Birmingham Central Strike Bulletin no. 4, 8 May 1926 (Birmingham)
1926-05-08 "The Birmingham Central Strike Bulletin no. 4, 8 May 1926" [g0375001.jpg], 8 May 1926, Birmingham Trade Union Emergency Committee Local Organisation